Direct role of interrod spacing in mediating cell adhesion on Sr-HA nanorod-patterned coatings - Zhou J (Dove Medical Press, 2014)
Jianhong Zhou,1 Yong Han,1 Shemin Lu2 1State Key Laboratory for Mechanical Behavior of Materials, 2Department of Genetics and Molecular Biology, College of Medicine, Xi'an Jiaotong University, Xi'an, People's Republic of China Abstract: The process in which nanostructured surfaces mediate cell adhesion is not well understood, and may be indirect (via protein adsorption) or direct. We prepared Sr-doped hydroxyapatite (Sr1-HA) 3D nanorods (with interrod spacing of 67.3±3.8, 95.7±4.2, and 136.8±8.7 nm) and 2D nanogranulate patterned coatings on titanium. Employing the coatings under the same surface chemistry and roughness, we investigated the indirect/direct role of Sr1-HA nanotopographies in the regulation of osteoblast adhesion in both serum-free and serum-containing Dulbecco's Modified Eagle/Ham's Medium. The results reveal that the number of adherent cells, cell-secreted anchoring proteins (fibronectin, vitronectin, and collagen), vinculin and focal adhesion kinase (FAK) denoted focal adhesion (FA) contact, and gene expression of vinculin, FAK, and integrin subunits (α2, α5, αv, β1, and β3), undergo significant changes in the inter-nanorod spacing and dimensionality of Sr1-HA nanotopographies in the absence of serum; they are significantly enhanced on the <96 nm spaced nanorods and more pronounced with decreasing interrod spacing. However, they are inhibited on the >96 nm spaced nanorods compared to nanogranulated 2D topography. Although the adsorption of fibronectin and vitronectin from serum are higher on 136.8±8.7 nm spaced nanorod patterned topography than nanogranulated topography, cell adhesion is inhibited on the former compared to the latter in the presence of serum, further suggesting that reduced cell adhesion is independent of protein adsorption. It is clearly indicated that 3D nanotopography can directly modulate cell adhesion by regulating integrins, which subsequently mediate anchoring proteins' secretion and FA formation rather than via protein adsorption. Keywords: nanotopography, inter-nanorod spacing, osteoblast adhesion, integrin, anchoring protein secretion, focal adhesion